The use of honey in button battery ingestions: a systematic review - Yannick Michael Schmidt; Oliver Muensterer; Danielle Wendling-Keim (Frontiers Media S.A., 2023)
BackgroundButton battery (BB) ingestions may cause severe and possibly fatal complications, especially if the battery is located in the esophagus. The application of oral honey has recently been proposed by the National Capital Poison Center in the USA and in an ESPGHAN position paper in Europe, but clinical trials and experimental studies are limited. The goal of this systematic review was to analyze the evidence for this approach.Materials and methodsA systematic review of clinical trials and experimental studies on the oral application of honey after BB ingestion in children was performed. Inclusion criteria according to the PICO format were patient age 0-18 years, ingestion of BB, oral administration of honey or other substances, all in vivo and in vitro studies, as well as reported complication rate, esophageal injury, and mortality. A manual search in the databases MEDLINE, Web of Science and Cochrane was performed to identify relevant search terms to form the following queries and to construct the extensive search. Furthermore, the search was extended by using snowballing on the reports reference lists. The review is registered at Research Registry. The identifying number is reviewregistry1581.ResultsWe found four publications that investigated the effects of honey after button battery ingestion. Three of these presented experimental in vitro and in vivo results and one reported a clinical retrospective study of 8 patients.ConclusionFollow up studies are required to further elucidate the effectiveness of the treatment with honey. The time intervals in which the use of honey is effective is not clear. Furthermore, a physiological model is needed for in vitro testing, preferably mimicking peristalsis and dynamic flow of the applied substances. However, since it is easy to apply and of minimal risk in patients over one year of age, honey should be considered a possible treatment option during the interval between presentation and endoscopic removal of the retained BB.Systematic Review Registrationhttps://www.researchregistry.com/browse-the-registry#registryofsystematicreviewsmeta-analyses/registryofsystematicreviewsmeta-analysesdetails/643e9df96750410027ee11b0/, identifier: reviewregistry1581.